Outlook of Present Organic Agriculture Policies and Future Needs in Sri Lanka - S.H. Pushpa Malkanthi (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
Many countries are formulating organic agriculture or organic farming policies aimed at sustainable agricultural development. Therefore, the objectives of this study were: to understand the present situation of organic agriculture policies in Sri Lanka and also in other countries where successful organic agriculture is operating; identify problems in the organic agriculture sector; and suggest potential policy measures to be implemented in Sri Lanka in future. The research was conducted in two stages. In the first stage, a thorough literature review was conducted to study the suitable policies available in other countries and also in Sri Lanka at present. In the second stage, two field surveys were carried out using pre-tested questionnaires, from December 2019 to May 2020, in order to gather farmers’ and extension officers’ information related to organic farming policy suggestions. According to the findings of the literature review, organic systems in some countries are more integrated with national strategic plans and visions. Those governments are more involved in new initiatives and farmers are encouraged to go organic through reliable and feasible policies. Although Sri Lanka has a high potential for organic agriculture, at present it is at an initial stage. While most organic products in Sri Lanka go to the export market, a small portion is kept at local markets. Demand for organic products in export as well as domestic markets is increasing. Even though there are seven international food certification agencies operating in the country as external inspection and certification bodies, a limited number of accredited certifications exist for products on the domestic market. Results of the farmers’ survey showed that even if farmers have a significant level of knowledge, few of them practice organic farming due to several existing problems. Moreover, extension officers have also identified similar types of problems that are faced by the farmers related to organic farming. Evaluation of Strengths, Weaknesses, Opportunities and Threats (SWOT) related to organic agriculture in the country helped to identify key problems facing policy-makers when balancing the supply and demand sides of organic products. Also, in developing organic agriculture, an effective linkage and coordination among government and private participants is crucial. Therefore, in Sri Lanka in this context, strategic focus on policy support for organic agriculture is needed. Current organic farming programs need to be revised in order to formulate policies covering all areas related to production, handling, processing, certification, labeling and marketing, in order to bring the benefits of organic agriculture to farmers, marketers and consumers in a fair manner.